2022
DOI: 10.1007/s11065-022-09540-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation in Parkinson Disease: A Meta-analysis of the Long-term Neuropsychological Outcomes

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) or globus pallidum internus (GPi) improves motor functions in patients with Parkinson’s disease (PD) but may cause a decline in specific cognitive domains. The aim of this systematic review and meta-analysis was to assess the long-term (1–3 years) effects of STN or GPi DBS on four cognitive functions: (i) memory (delayed recall, working memory, immediate recall), (ii) executive functions including inhibition control (Color-Word Stroop test) and flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 123 publications
(272 reference statements)
2
26
0
1
Order By: Relevance
“…In some centres, a cutoff age for this procedure was decided at an age of 69-70 years. The third criterium for good outcome was a good cognition because it has been reported that cognitive decline could be exacerbated following STN DBS [71,72]; hence all patients referred for DBS undergo a neuropsychologic test to evaluate cognitive skills including memory and executive function. Finally, the last criteria is related to the mood of the patient, which should be formally evaluated in order to avoid performing STN DBS in patients with relevant or untreated depression.…”
Section: Stn Dbs For Pdmentioning
confidence: 99%
“…In some centres, a cutoff age for this procedure was decided at an age of 69-70 years. The third criterium for good outcome was a good cognition because it has been reported that cognitive decline could be exacerbated following STN DBS [71,72]; hence all patients referred for DBS undergo a neuropsychologic test to evaluate cognitive skills including memory and executive function. Finally, the last criteria is related to the mood of the patient, which should be formally evaluated in order to avoid performing STN DBS in patients with relevant or untreated depression.…”
Section: Stn Dbs For Pdmentioning
confidence: 99%
“…21 The results of the present study showed a significant effect on memory in PD patients treated with STN-DBS, consistent with the findings of an earlier report. 22 Implicit memory is defined as the acquisition of knowledge that occurs without conscious recollection, and it is critical for cognitive function. Implicit memory was more severely affected in the PIGD group compared with TD patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still uncertainty about how DBS can negatively impact cognition and behavior in some patients. It has been suggested that in some instances, neurosurgical implantation can be detrimental, especially in patients with presurgical cognitive impairment (18). A prospective study assessing motor and nonmotor outcomes of PD-GBA1 treated either with STN-or GPi-DBS and stratified for the different variants is warranted.…”
Section: The Role Of Dbs Targetmentioning
confidence: 99%